Score for the Group SL(2,38) - Jasim, Niran sabah; Lfta , Mohammed Ibrahem; Issa , Ahmad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The set of all (n×n) non-singular matrices over the field F. And this set forms a group under the operation of matrix multiplication. This group is called the general linear group of dimension  over the field F, denoted by . The determinant of these matrices is a homomorphism from  into F* and the kernel of this homomorphism was the special linear group and denoted by  Thus  is the subgroup of  which contains all matrices of determinant one.The rationally valued characters of the rational representations are written as a linear combination of the induced characters for the groups discussed in this paper. We find the Artin indicator for this group after studying the rationally valued characters of the rational representations and the induced characters.